Digital Entrepreneurship Education and Entrepreneurial Creativity Among Generation Z: The Mediating Roles of Social Media and Entrepreneurial Intuition - Andika Isma; Halim Dwi Putra; Maya Sari; Susatyo Adhi Pramono; Betania Kartika Muflih (Universitas Negeri Makassar, 2026)
Digital entrepreneurship education is considered important for enhancing the entrepreneurial creativity and digital capabilities of Generation Z in promoting entrepreneurial activities through social media platforms. This study aims to analyze the effect of digital entrepreneurship education on the creativity of Generation Z in promoting businesses through social media, with entrepreneurial intuition serving as a mediating variable. This study employed a quantitative research approach using Partial Least Squares Structural Equation Modeling (PLS-SEM) as the analytical technique. Data were collected through questionnaire distribution involving 700 Generation Z respondents in Indonesia. The findings indicate that digital entrepreneurship education, social media utilization, and entrepreneurial intuition have positive and significant effects on entrepreneurial creativity among Generation Z entrepreneurs in promoting businesses through social media. The results also reveal that entrepreneurial intuition and social media play important mediating roles in strengthening the relationship between digital entrepreneurship education and entrepreneurial creativity. These findings suggest that digital entrepreneurship education contributes not only to improving entrepreneurial knowledge but also to strengthening creativity, business intuition, and digital promotional capabilities among young entrepreneurs. Therefore, the development of practical entrepreneurship curricula integrated with social media utilization and entrepreneurial intuition training is essential to support the growth of innovative and competitive young entrepreneurs in the digital era.